The empathetic mind: the essence of human spirituality - Souza, Marian de (International journal of children's spirituality, 2014)
The discovery of mirror neurons has led to some exciting research into the role of the brain and human empathy. Empathy is a significant element in human relationality and, therefore, human spirituality. This article will focus on the links between mirror neurons and human empathy and education. It will then examine how technology may be a factor in causing the erosion of empathy in today’s world, leading to school violence and bullying. It will conclude by offering some guidelines for educational programmes which may lead to the nurturing of children’s empathy.